2018
DOI: 10.1002/iub.1879
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐98 attenuates cardiac ischemia‐reperfusion injury through inhibiting DAPK1 expression

Abstract: Cardiovascular ischemic disease is a large class of diseases that are harmful to human health. The significant role of microRNAs (miRNAs) in terms of controlling cardiac injury has been reported in latest studies. MiR‐98 is very important in regulating the apoptosis, the differentiation, the growth as well as the metastasis of cells. Nevertheless, the effect of miR‐98 in the cardiac ischemia reperfusion (I/R) injury has rarely been investigated. In the current research, we found that the miR‐98 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Post-treatment with carvacrol also promoted an increase in the expression of the DAPK1 gene and a decrease in the enzyme PPP2R2A ( Li et al, 2019 ). DAPK1 is a serine/threonine kinase, a tumor suppressor protein that promotes apoptosis ( Agodi et al, 2015 ; Zhai et al, 2019 ), while PPP2R2A, a regulatory subunit of protein phosphatase 2A (PP2A), controls the pathway of AKT signaling associated with tumor growth ( Wang et al, 2016 ; Zeng et al, 2016 ). In fact, both may be involved in a possible antitumor mechanism of carvacrol, but it is still not very clear, requiring further studies ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment with carvacrol also promoted an increase in the expression of the DAPK1 gene and a decrease in the enzyme PPP2R2A ( Li et al, 2019 ). DAPK1 is a serine/threonine kinase, a tumor suppressor protein that promotes apoptosis ( Agodi et al, 2015 ; Zhai et al, 2019 ), while PPP2R2A, a regulatory subunit of protein phosphatase 2A (PP2A), controls the pathway of AKT signaling associated with tumor growth ( Wang et al, 2016 ; Zeng et al, 2016 ). In fact, both may be involved in a possible antitumor mechanism of carvacrol, but it is still not very clear, requiring further studies ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the inhibition of miR‐1 may have protective effects on myocardial I/R injury . According to recent reports, miR‐98 expression was downregulated in cardiomyocytes undergoing H/R . Zhu et al hold the view that miR‐499 protected the rat heart against I/R injury through inhibiting apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…10 According to recent reports, miR-98 expression was downregulated in cardiomyocytes undergoing H/R. 11 Zhu et al hold the view that miR-499 protected the rat heart against I/R injury through inhibiting apoptosis. 12 So miRNAs may be proposed as diagnostic tools and novel biomarkers for cardiomyocyte.…”
mentioning
confidence: 99%
“…Numerous miRNAs had been reported to be up-or down-regulated in patients with myocardial ischemia/reperfusion injury (Table 1). Among them, MiR-22, miR-134, miR-135a, miR-203, miR-144, miR-98, miR-18a, miR-210, miR-340-5p, miR-374a-5p, and miR-1192 exert protective effects in cardiovascular ischemic injury through downregulating their target genes [37,41,56,77,79,112,160,163,175,183,184]. On the other hand, a specific set of miRNAs has been linked to cardiac dysfunctions in varied cardiac injury models.…”
Section: Roles Of Mirnasmentioning
confidence: 99%